Identification of Cleavage Sites Recognized by the 3C-Like Cysteine Protease within the Two Polyproteins of Strawberry Mottle Virus - Mann, Krin S.; Walker, Melanie; Sanfaçon, Hélène (Frontiers in Microbiology, 2017)
Strawberry mottle virus (SMoV, family Secoviridae, order Picornavirales) is one of several viruses found in association with strawberry decline disease in Eastern Canada. The SMoV genome consists of two positive-sense single-stranded RNAs, each encoding one large polyprotein. The RNA1 polyprotein (P1) includes the domains for a putative helicase, a VPg, a 3C-like cysteine protease and an RNA-dependent RNA polymerase at its C-terminus, and one or two protein domains at its N-terminus. The RNA2 polyprotein (P2) is predicted to contain the domains for a movement protein and one or several coat proteins at its N-terminus, and one or more additional domains for proteins of unknown function at its C-terminus. The RNA1-encoded 3C-like protease is presumed to cleave the two polyproteins in cis (P1) and in trans (P2). Using in vitro processing assays, we systematically scanned the two polyproteins for cleavage sites recognized by this protease. We identified five cis-cleavage sites in P1, with cleavage between the putative helicase and VPg domains being the most efficient. The presence of six protein domains in the SMoV P1, including two upstream of the putative helicase domain, is a feature shared with nepoviruses but not with comoviruses. Results from trans-cleavage assays indicate that the RNA1-encoded 3C-like protease recognized a single cleavage site, which was between the predicted movement protein and coat protein domains in the P2 polyprotein. The cleavage site consensus sequence for the SMoV 3C-like protease is AxE (E or Q) / (G or S).